The Curious Human Knee - Yu, Han (Columbia University Press, 2023)
Where would we be without the knee? This down-to-earth joint connecting the thigh and the lower leg doesn't receive the attention it deserves. Yet, as The Curious Human Knee reveals, it is crucial to countless facets of science, medicine, culture, and history-and even what makes us human.Science writer Han Yu provides an informative, surprising, and entertaining exploration of the human knee across time and place. She begins with our earliest ancestors, emphasizing that walking upright separates us from the apes and bipedal knees appeared long before big brains and sophisticated tools. Yu considers the intricate anatomy of the knee, its evolutionary history, and the complexity of treating knee pain, including her own. She examines why women's knees might be more prone to damage than men's and addresses the roles of race and class in ailments such as osteoarthritis. The book gets knee-deep into an astonishing range of topics-fashion from flappers to miniskirts and ripped jeans, cultural practices spanning Japanese knee walking and Thai boxing. Yu reflects on the symbolic power of kneeling from the imperial court in China to the football field in the United States and shows why the knee figures into so many social and political phenomena.Distilling a vast amount of research in a style that is engaging, conversational, and even personal and witty, this book opens readers' eyes to the complexity and significance of the humble knee